Factors Influencing ChatGPT Adoption by Generation Z Students in Higher Education: Enhancing Academic Activities in Indonesia - Palangan, Citra Yayu'; Frederik, Raymond (Universitas Sarjanawiyata Tamansiswa, 2024)
his research investigates the factors influencing Gen Z students' adoption of ChatGPT in higher education to enhance academic productivity. It uses the Technology Acceptance Model (TAM) framework as a fundamental theory to predict the acceptance of new technology, which consists of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) as main factors. Furthermore, this research adds two additional factors: Social Influence (SI) and Competitive Pressure (CP). Therefore, this research uses four hypotheses as potential factors influencing ChatGPT adoption and includes TAM, UTAUT and TOE as the theory of the theoretical model. As a result, it provides a conceptual model and needs validation through future research involving specific Gen Z students in higher education. This research recommends using a population for all students who have adopted ChatGPT in Indonesia.